Association of steroid use with survival in solid tumours. (December 2020) - Petrelli, Fausto; Bukovec, Roberta; Perego, Gianluca; Luisa, Roncari; Luciani, Andrea; Zaniboni, Alberto; Ghidini, Antonio
Abstract: Background: Steroids are commonly used in patients with solid tumours for supportive therapy. In other cases, they are an essential part of cancer treatment such as prostate cancer. Some preclinical observations lead to the notion that glucocorticoids may modulate growth factors' pathways and may induce the progression of cancers. Glucocorticoids are associated with several side-effects on many organ systems (e.g. serious infections, diabetes, sepsis and thrombosis). We have performed a systematic review and meta-analysis to evaluate the outcome of cancer patients that assume or not steroids. Methods: Published articles that evaluated survival associated with steroids use in cancer patients from inception to June 2020 were identified by searching the PubMed, EMBASE and Cochrane Library databases. The primary outcome of interest was the risk of death, and the secondary end-point was the risk of progression in steroid versus non-steroid users. Results: Seventy-six studies were in quantitative synthesis for a total of 83, 614 patients. Use of steroids was associated with a reduced survival (hazard ratios (HR) = 1.18, 95% confidence interval (CI): 1.1–1.26; P  < .01). Progression-free survival was also decreased in steroid versus non-steroid users (HR = 1.13, 95% CI: 1.01–1.26; P = .03). In patients with lung cancer, advanced disease and supportive care indications were settings where the use of steroids increased the risk of death. Conclusions: In patients with advanced cancers, use of steroids should be reduced and, at best, avoided because it may reduce survival, in particular, for patients with lung cancer and for palliative/supportive care purposes. Highlights: Steroids are commonly used in patients with solid tumors for supportive therapy. We evaluated the outcome of cancer patients that assume or not steroids. Use of steroids was associated with a reduced survival (HR = 1.18, 95%CI 1.1–1.26; P<.01). Use of steroid should be reduced and at best avoided because it may reduce survival.